Using ADDIE Approach to Design English Language Teaching Material for Islamic Economics - Riska; Misbah Fikrianto; Muhammad Yaumi (Nusantara Science and Technology Proceedings, 2024)
This study aimed at producing English language module for the Islamic economics buy using ADDIE approach. In collecting data, the researchers used two instruments that consisted of an interview and an evaluation checklist. In this study, data collection procedures included analyzing the students’ needs through the result of previous research and the result of interview that discussed need analysis of English for Islamic Economics department, designing syllabus and prototype material 1, developing English materials and evaluating or validating the materials by experts. The result indicated that the students of Islamic Economic department need English instructional material that integrated with English skills and contains material about Islamic Economics, such as income distribution and consumption. Based on the result of expert evaluation, it determined that the syllabus and each part of the material in the module had been well developed and following the students’ needs, and the product can be used as a guide for learning English in Islamic Economics department.